Three Rejoinders in Search of an Author - Craig Howley; Aimee Howley; Jacqueline Yahn (Journal of Research in Rural Education, 2014)
The three rejoinders that follow engage ideas in Amy Azano's critique (q.v.) of our study of dissertations with a dual focus on rural education and curriculum and instruction (C&I). The journal editors invited a rejoinder to the critique, and we have provided three of them, offered as anonymous, but playfully, for reasons we explain next.